All-Negro comics : America's first Black comic book - Robinson, Chris (Comic book editor); Evans, George J., Jr; Terrell, John (Comic book artist); Smith, William H.; Cooper, Leonard (Comic book artist); Whitted, Qiana J., 1974-; Brothers, David (Comics author); Pryor, Shawn; Peters, Micah; Smith, Zipporah; Guzmán, Samatha; Hatcher, Jasmine; et al. (Image ANC75, 2025)
"In 1947, groundbreaking journalist Orrin C. Evans assembled a team of Black cartoonists to publish All-Negro Comics, the first comic book created by Black artists for Black readers of all ages. Almost a century later, All-Negro Comics #1 is a little-known relic instead of an American heirloom like Action Comics #1, Marvel Comics #1, and other milestone comic books from the era. All-Negro Comics 75th Anniversary Edition preserves that history for generations to come, containing All-Negro Comics #1, in full and digitally remastered for clarity, several essays for historical context and con temporary reflection, as well as new stories by Black writers and artists of today, featuring the original characters." -- Back cover.